Biocompatibility of Ferrara intracorneal ring segment with and without chondroitin sulfate coating: Clinical and histopathological evaluation in rabbits - Andreghetti, Eduardo [UNESP]; Hashimoto, Miriam [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Antunes, Vitor Andrigheti Coronado [UNESP]; Segundo, Paulo de Souza [UNESP]; Silva, Maria Rosa Bet de Moraes [UNESP] (FapUNIFESP (SciELO), 2013)
PURPOSE: To investigate and compare the biocompatibility of two types of Ferrara intracorneal ring segment: with and without chondroitin sulfate coating by clinical and histopathological evaluation. METHODS: A randomized experimental study was carried out on thirty right-eye corneas from 30 Norfolk albino rabbits allocated into two experimental groups: Group G1 - implanted with Ferrara intracorneal ring segment without coating (FICRS) and Group G2 - implanted with Ferrara intracorneal ring segment with chondroitin sulfate coating (FICRS-CS). Left eyes formed the control group. Clinical parameters analyzed were: presence of edema, vascularization, infection and ring extrusion one, 30, and 60 days after surgery. Histopathological parameters analyzed were: number of corneal epithelial layers over and adjacent to the ring, presence of spongiosis, hydropic degeneration, basement membrane thinning, inflammatory cells, neovascularization and pseudocapsule formation. RESULTS: At clinical examination 60 days after implant, edema, vascularization and extrusion were observed respectively in 20%, 26.7%, 6.7% of FICRS corneas and in 6.7%, 6.7%, and 0% of FICRS-CS corneas. Histopathological evaluation showed epithelial-layer reduction from 5 (5;6) to 3 (3;3) with FICRS and from 5 (5;5) to 4 (3;5) with FICRS-CS in the region over the ring. Epithelial spongiosis, hydropic degeneration, and basement membrane thinning were present in 69.2%, 53.8%, and 69.2% of FICRS and in 73.3%, 73.3%, and 46.7% with FICRS-CS, respectively. Vascularization was present in 38.5% of FICRS and 13.3% with FICRS-CS, inflammatory cells in 75% of FICRS and 33.3% with FICRS-CS, and pseudocapsule in 66.7% of FICRS and 93.3% with FICRS-CS. Giant cells occurred only in the FICRS-CS group (20%). CONCLUSION: Ferrara intracorneal rings coated with chondroitin sulfate (FICRS-CS) caused lower frequency of clinical and histopathological alterations than Ferrara intracorneal rings without the coating (FICRS), demonstrating higher biocompatibility of the FICRS-CS.
Keywords: Chondroitin sulfates; Cornea; Corneal neovascularization; Prosthesis implantation; Rabbits; chondroitin sulfate; animal experiment; animal tissue; biocompatibility; controlled study; cornea neovascularization; corneal pachymetry; edema; epithelium cell; female; giant cell; histopathology; inflammatory cell; intrastromal corneal ring segment; nonhuman; postoperative complication; rabbit